New Proxy Blind Multi Signature based on Integer-Factorization and Discrete-Logarithm Problems - Swati Verma; Birendra Kumar Sharma (Institute of Advanced Engineering and Science, 2012)
Digital proxy multi-signature and blind signature scheme are found very useful for the purpose of electronic voting and electronic cash transaction. In proxy multi-signature, many original signers can delegate their signing power to a proxy signer in such a way that the proxy signer can sign any message on behalf of original signers. In blind signature, the signer cannot make a linkage between the blind signature and the identity of the requester. Proxy blind multi-signature is the combination of proxy multi-signature and blind signature. In this paper, we propose a new proxy blind multi-signature scheme based on integer factorization problem (IFP) and discrete logarithm problem (DLP) to improve the security aspect. It satisfies the security properties of both the blind signature and the proxy multi-signature scheme.